DAMPAK PENGELOLAAN SAMPAH DI TPA PADA KESEHATAN MASYARAKAT - Emilda, Emilda; Septiani, NAP; Pratiwi, RH (Jurnal Ilmiah Ilmu Kesehatan: Wawasan Kesehatan, 2019)
The limitations of waste management in the Cipayung Landfill (TPA) causing a buildup of garbage up to more than 30 meters. This condition has a health impact on people in Cipayung Village. This study aims to analyze the impact of waste management at Cipayung Landfill on public health in Cipayung Village, Depok City. The research is descriptive qualitative. Data obtained by purposive sampling. Data was collected by interviews, observation and documentation. Based on interviews with 30 respondents, it was found that the most common diseases were diarrhea, then other types of stomach ailments, subsequent itching on the skin and coughing. This is presumably because the environmental conditions in the form of unhealthy air and water and clean and healthy living behaviors (PHBS) have not become the habit of the people. The results indicated that there were no respondents who had implemented all of these criteria. In general respondents have implemented  3 criteria, namely maintaining hair hygiene, maintaining skin cleanliness, and maintaining hand hygiene. While maintaining clean water storage is the most often overlooked behavior. To minimize this health impact, improvements in waste management in Cipayung landfill are needed along with continuous socialization and education to develop PHBS habits and the importance of maintaining a clean environment.